INFN muon tomography demonstrator: past and recent results with an eye to near-future activities. (10th December 2018) - Checchia, P.; Benettoni, M.; Bettella, G.; Conti, E.; Cossutta, L.; Furlan, M.; Gonella, F.; Klinger, J.; Montecassiano, F.; Nebbia, G.; Pegoraro, M.; Pesente, S.; et al.
Abstract : A short description of the muon tomography demonstrator at the INFN Laboratori Nazionali di Legnaro near Padua, Italy, is given and the principal achievements owing to the data collected at that experimental facility are presented. In particular, the feasibility studies for several applications based on the muon-tomographic technology, within national and European projects, are discussed. The experimental problems and the procedures used to improve the performance are underlined. In addition, new activities and the related detector optimization are illustrated. This article is part of the Theo Murphy meeting issue 'Cosmic-ray muography'.